Pengembangan Standard Empiris Efikasi Penerangan Listrik Untuk Mendukung Perhitungan Cepat Dalam Perancangan Instalasi Listrik - Tiyono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
In the process of drafting/design of electrical installations, especially in the design calculations required the installation of electric lighting fast, to soon be able to provide information about the equipment, technology, power requirements and cost required. Standard empirical efficacy of electric lighting that matches the tropics, is required to support rapid decision-making calculations, can immediately provide information about the equipment, technology, power requirements and cost involved as well as the consideration of energy-saving insights along with the development of the concept of "green building". How research includes surveys various decades building lighting intensity at UGM, spacious room, and satisfaction taste the intensity of lighting in a variety of activities. Finally, the activities of the test samples lighting, to find the type of lights that have high efficiency. From data surveys computed lighting efficacy values for the various buildings. With the analysis of generalization and priorities, both efficacy data and appetite satisfaction, priority parameter can be found. Based on priorities parameters can be made standard empirical efficacy lighting equipment, in 6 status, namely: 1. poorly (< 2W/m2), 2. most economically (between 2 W/m2 and 3 W/m2), 3. economically (between 3W/m2 and 7.5 W/m2), 4. ideally (between 7.5 W / m2 and 11W/m2), 5. luxurious (between 11W/m2 and 15W/m2) or 6. extravagant (> 15W/m2). In the hope the results of this research can be used to help solve the duration problems of electrical installation design.